Chronic non-suppurative mandibular osteomyelitis: case report - Cazar Almache, Marcelo Enrique (2022)
Osteomyelitis (OM) is considered one of the most challenging medical conditions for surgeons. In the last 50 years the number of cases of maxillary OM has decreased due to an improvement in oral hygiene, however, its complication is still relevant. The purpose of this paper is to present a case report of a patient with mandibular osteomyelitis and to analyze the literature on this condition.